2020
DOI: 10.21203/rs.3.rs-51674/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic analysis of rice seedling traits related to machine transplanting under different seeding densities

Abstract: Background: Due to the diversity of rice varieties and cropping systems in China, the limitation of seeding density and seedling quality makes it hard to improve machine-transplanted efficiency. Previous studies have shown that indica and japonica varieties varied in machine transplanting efficiency and optimal seeding density. In this study, a RIL population derived from ‘9311’ and ‘Nipponbare’ were performed to explore the seedling traits variations and the genetic mechanism under three seeding densities. Re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Rice is one of the most widely planted crops, with over 158 million hectares planted globally and an annual output of more than 700 million tons, which is critical for food production safety. 15,16 However, as common weeds in paddy fields, weeds such as barnyard grass can cause yield losses of 40-60% in competition with rice, and even up to 90% if not properly controlled. 17 Pre (2-chloro-N-(2,6-diethylphenyl)-N-(2propoxyethyl) acetamide), belongs to the class of chloroacetanilide herbicides and is widely used as a preemergence herbicide for the control of weeds such as barnyard grass in the paddy field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rice is one of the most widely planted crops, with over 158 million hectares planted globally and an annual output of more than 700 million tons, which is critical for food production safety. 15,16 However, as common weeds in paddy fields, weeds such as barnyard grass can cause yield losses of 40-60% in competition with rice, and even up to 90% if not properly controlled. 17 Pre (2-chloro-N-(2,6-diethylphenyl)-N-(2propoxyethyl) acetamide), belongs to the class of chloroacetanilide herbicides and is widely used as a preemergence herbicide for the control of weeds such as barnyard grass in the paddy field.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we aimed at the acidic conditions of paddy fields (pH 5.0-pH 6.5), based on the CRF strategy and increased drug utilization, by using the acid-responsive material ZIF-67, a Co-based MOF, as the carrier, the small molecule pesticide Pre was encapsulated inside, and the safener AD-67 was self-assembled on the surface to form a pH double controlled release system AD-67@Pre@ZIF-67 (Scheme 1), which achieved the characteristics of partially releasing AD-67 first and then disintegrating the material to release Pre. Studies have shown that pH values between 5.0-6.5 can ensure the normal growth of rice, 16 and the growth of seedlings in this pH range results in good nutrient absorption capacity and strong photosynthesis, and physiological metabolism. 42 In this study, the pH range of the paddy field was simulated.…”
Section: Introductionmentioning
confidence: 99%